Advanced Methodologies for Trace Elements in Edible Oil Samples: A Review. (3rd October 2022) - Shah, Nasrullah Syed; Soylak, Mustafa
Abstract: Advanced methodologies were applied for the detection of some elements at trace levels in edible oils. Trace elements play a role in oil stability, quality of edible oils and fats. In the present study, problems were addressed related to simple, cheap, less time consuming and suitable pretreatment advanced methods for suitable sample introduction and calibrations as well as the strategies and techniques are discussed. The present review is aimed to discuss the significance of simplifying sample treatments are offered for trace elements in oils. The period covered by this review is last twenty years. However, the various applications of advanced methodologies including extraction and microextraction. The scope of spectrometric techniques used for the analysis of trace elements in edible oils was discussed by new instrumental development trends.